2014
DOI: 10.4137/cmc.s14320
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Echocardiography Abnormalities among 168 Consecutive Referrals to an Urban Private Hospital in South-Western Nigeria

Abstract: Trans-thoracic echocardiography (TTE) is an important non-invasive cardiac examination that provides structural and functional information. It is useful in the diagnosis of cardiac diseases and often guides the management and follow-up of patients with cardiovascular diseases (CVD).The study aimed to present an audit of the echocardiograms performed in an urban private hospital over a two-year period in order to define the pattern of cardiac diseases in our center. Echocardiogram reports of 168 consecutive pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This is comparable to the findings of Oyedeji et al, where hypertension was the most common indication for ECHO. 10 The percentage of 16.1% is however much lower than that in Cuspidi et al (30.4%). 11 This is likely due to the fact that Hypertension and Article hypertensive heart disease are separate indications in this study (as compared to theirs), with both having a combined prevalence of 24.6%.…”
Section: Discussionmentioning
confidence: 63%
“…This is comparable to the findings of Oyedeji et al, where hypertension was the most common indication for ECHO. 10 The percentage of 16.1% is however much lower than that in Cuspidi et al (30.4%). 11 This is likely due to the fact that Hypertension and Article hypertensive heart disease are separate indications in this study (as compared to theirs), with both having a combined prevalence of 24.6%.…”
Section: Discussionmentioning
confidence: 63%
“…We found a prevalence of 4.24%, whereas previous research found frequencies ranging from 0.4% to 2.4%. [ 35 ] The low risk of VHD may be owing in part to the study's inclusion of only adults.…”
Section: Discussionmentioning
confidence: 99%
“…Low-income countries struggle with lower income per capita and less Magnetic Resonance Imaging (MRI) units per million population, for example, Mexico, Ghana, Sub-Saharan Africa, Colombia, and India have 2.9, 0. [72]. In a country where there are limited diagnostic facilities, echocardiograms could be used for the classification of HCM and for monitoring patients [73].…”
Section: Study Low-income Country High-income Countrymentioning
confidence: 99%